Opposing sound shifts involving alveolar and palatal clicks (ǃ ~ ǂ) in the ǃUi subgroup of TUU languages from southern Africa - du Plessis, Menán (Stellenbosch Papers in Linguistics Plus, 2023)
Peer-reviewed snippet